Advances in Surface Laser Cladding Remanufacturing of Shaft Parts - Zhao, Changlong; Yang, Junbao; Li, Ming; Zhao, Qinxiang; Ma, Hongnan; Jia, Xiaoyu; Zhang, Haifeng (Manufacturing Technology Journal, 2023)
This paper provides an overview of the commonly used processes and equipment for laser cladding, including pre-set powder feeding, simultaneous powder feeding, wire feeding cladding, and coaxial cladding nozzles. By comparing the above processes and related nozzles, the coating characteristics are summarized for the selection of appropriate methods and equipment in different working environments. Meanwhile, the morphology and properties of the clad layers of shaft parts processed with different process parameters (e.g. laser power, scanning speed, lap rate, powder feed rate) and the influence of the combined parameters are overviewed. The changes and mechanisms of metals, ceramics, and metal-ceramic composites in terms of hardness, wear resistance, metallurgical bonding, and microstructure are analyzed. In addition, the application of numerical simulation techniques to simulate the temperature and stress fields and to plan the melting trajectory when laser cladding processing is performed on the surface of shaft parts are reviewed. Finally, the problems in the current research on laser cladding of shaft parts are summarized and the development directions are discussed.
Keywords: Shaft part; Laser cladding; Process parameters; Cladding materials